Asevelvollisuuden kustannukset - Ville Kaitila; Niku Määttänen (The Research Institute of the Finnish Economy (ETLA), 2021)
– We describe the costs of the conscription system from different perspectives. In particular, we consider the definition of opportunity cost related to the service time of conscripts. This is a cost that is not directly reflected in the state budget. In addition, we review related literature and present calculations on the current costs of conscription in Finland.
Keywords: H41; J24; 330; National defence; Conscription; Opportunity cost